Portrait du philosophe en écrivain : une lecture écopoétique de l’oeuvre de Gaston Bachelard - Barontini, Riccardo (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
This article focuses on the relevance of Bachelard’s work for the critical discourse on literature and ecology, while proposing an unprecedented interpretation of his production as a writer of nature. Three fundamental theoretical elements are presented: Bachelard’s unprecedented attention to the link between matter and the imaginary; his phenomenology of dwelling and his reflection on the imaginary of places; his theorization of the poietic dimension of the imagination, which can modify the way we situate ourselves in the world. This article is based on the idea that these theoretical elements assume a lyrical incarnation in the passages in which Bachelard employs subjective experiences in order to justify his philosophical undertaking. These texts are interpreted by using the tools of ecopoetics, through a reading that focuses on the literary dimension of Bachelard’s writing, that shows its complementarity with philosophical discourse. Keywords: Bachelard, ecocriticism, lyricism, nature writing, ecology.